Ch’Ixi Animals in Two Environmental Conflicts: Evocations of Humboldt Penguins and Huemuls - Baigorrotegui-Baigorrotegui, G (Routledge, 2024)
The agency of animals in technoscience has been much debated in science and technology studies, animal studies, and environmental collective action studies. In particular, the prominence of animals as mediators in environmental conflict opens avenues for dialogue with perspectives from the Global South, especially in the face of persistent colonial mining-energy regimes. The evocation of human-animal encounters contributed to the closure of two electricity generation projects in Chile and provided an insight into the surprises and complications of the inclusion of animal species–huemuls and Humboldt penguins–in distinct environmental campaigns. Although the influence of such ‘charismatic’ animals stands out as a fruitful approach to understanding the role of animals in environmental conflicts, it is helpful to consider alternative anti-colonial perspectives from the global South. In particular, the ch ixi metaphor of the Aymara people–representing the politics of beings resulting from the juxtaposition of antagonistic realities, or what is and is not at the same time–creates productive frictions in human-animal encounters that differs from the notion of charismatic animals as mediators, especially when it comes to modes of resistance by local communities. This perspective recognizes the differentiated strength of the semiotic-material mediations of nonhumans that can emerge from human-animal ch ixi encounters in collective environmental actions. © 2024 Process Press.